In vitro evaluation of the antibacterial activity of some medicinal plant extracts against Xanthomonas campestris pv. musacearum - Yemata, Getahun; Fetene, Masresha (Ethiopian Journal of Science and Technology, 2025)
Enset bacterial wilt caused by Xanthomonas campestris pv. musacearum (Xcm) is a destructive disease of Ensete ventricosum (Welw.) Cheesman) in Ethiopia. The antibacterial activities of methanol leaf extracts of Achyranthes aspera, Agarista salicifolia, Datura stramonium, Melia azedarach, Pycnostachys abyssinica and Vernonia amygdalina were evaluated in vitro against Xcm. Fresh leaves were collected, dried under shade and ground to fine powder. Extraction was carried out using maceration method. The antibacterial activity of extracts was evaluated by disc diffusion method. Total phenolics content was estimated using Folin Ciocalteau method. The result revealed that higher percent extract yield was obtained from A. salicifolia followed by P. abyssinica. Extracts of all species showed antibacterial activity except M. azedarach. Significant differences in inhibition zone diameter were recorded between species and among test concentrations. The widest inhibition zone was recorded by A. salicifolia followed by P. abyssinica. Unlike others, extract of A. salicifolia had abundant amount of alkaloids, flavonoids, phenols, terpenoids, saponnins, tannins and cardiac glycosides. The remaining species lacked one or more of these metabolites and the existing ones occurred either in small or moderate amount. Moreover, the extract of A. salicifolia was found to have the highest total phenolics content and this was positively correlated with inhibition zone diameter at all test concentrations suggesting its potential antibacterial activity. This shows that the extract of A. salicifolia has the potential for further bioformulation and commercialization as biocide with broad spectrum activity. However, further research should be conducted to identify the active compounds responsible for such antibacterial activity.